Effects of 12-Week Multivitamin and Omega-3 Supplementation on Micronutrient Levels and Red Blood Cell Fatty Acids in Pre-menopausal Women - Osburn, Shelby C.; Roberson, Paul A.; Medler, Jessica A.; Shake, Jacob; Arnold, Robert D.; Alamdari, Nima; Bucci, Luke R.; Vance, Arianne; Sharafi, Mastaneh; Young, Kaelin C.; Roberts, Michael D. (Frontiers in Nutrition, 2021)
We examined if a multivitamin-mineral and omega-3 supplement (MV) affected serum micronutrient levels and red blood cell omega-3 fatty acid profiles in pre-menopausal females. Women (21-40 years old) who were apparently healthy were recruited from the local community (ClinicalTrials.gov trial registration NCT03828097). Pretesting (PRE) occurred in the morning 5±2 days following each participant’s menses and involved a fasted blood draw, body mass assessment, and blood pressure assessment. Participants were then randomly assigned in a double-blinded fashion to either the MV (n=43) or placebo group (n=51). Participants consumed two capsules per day with breakfast for 12 weeks. Following the trial, participants reported to the laboratory for POST assessments, which replicated PRE procedures. Red blood cell fatty acid and serum micronutrient analyses were performed in a blinded fashion at hematology laboratories. A group×time interaction was observed for serum vitamin D levels (p<0.001). MV increased levels from PRE to POST (+43.7%, p<0.001), whereas no change occurred in the placebo group. Additionally, 78% of MV participants at PRE exhibited inadequate Vitamin D levels (<40 ng/dL), whereas only 30% exhibited levels below this threshold at POST. An interaction was also observed for serum folate levels (p<0.001). MV increased serum folate from PRE to POST (p<0.001), whereas no change occurred in the placebo group. Red blood cell omega-3 fatty acid content increased from PRE to POST in the MV group (p<0.001) and placebo group (p<0.05), although POST values were greater in the MV group (p<0.001). An interaction was observed for serum HDL cholesterol levels (p=0.047), and a non-significant increase in this variable from PRE to POST occurred in the MV group (p=0.060). Four-day food recalls indicated MV increased intake of omega-3 fatty acids, vitamin D, folate, and other micronutrients. In summary, MV supplementation increased serum vitamin D, serum folate, and red blood cell omega-3 fatty acid levels. However, these data are limited to healthy females, and more research is needed to examine if MV can affect metabolic disturbances in individuals with micronutrient deficiencies.